Non-positive experiences encountered by pupils during participation in a mindfulness-informed school-based intervention - Miller, EJ; Crane, C; Medlicott, E; Robson, J; Taylor, L (Springer, 2023)
Mindfulness-informed school-based mental health curricula show much promise in cultivating a positive school climate which supports the well-being and mental health of pupils and staff. However, non-positive pupil outcomes and experiences of school-based mental health interventions are often under-recognised and under-reported. This study sought to capture non-positive pupil experiences of a popular mindfulness-informed curriculum. Some pupils across all schools in the study described non-positive experiences, including having troubling thoughts and emotions, and not finding the programme effective. Contexts surrounding these experiences are explored and linked to existing literature, and subsequent recommendations for improvements are made, including the importance of having clear programme structure, definitions and aims, acknowledging and accommodating fidelity issues as best as possible, and better highlighting the potential for non-positive experiences and how they may be reduced.